Conflict of Interests : Organized Labor and the Civil Rights Movement in the South, 1954-1968 - Draper, Alan (Book collections on Project MUSE., 2018)
On the basis of extensive archival research, Alan Draper illuminates the role organized labor played in the southern civil rights movement. He documents the substantial support the AFL-CIO and its southern state councils gave to the struggle for black equality, suggesting that labor's political leadership recognized an opportunity in the civil rights movement. Frustrated in their efforts to organize the South, labor leaders understood the potential of newly enfranchised blacks to challenge conservative southern Democrats.At the same time, white union members in the South were more interested in defending their racial privileges than in allying themselves with blacks. An explosive tension developed between labor's political leadership, desperate to create a party system in the South that included blacks, and a rank and file determined to preserve southern Democracy by excluding blacks. This book looks at the ways that tension was expressed and ultimately resolved within the southern labor movement.